Learning Environment and Learning Facilities: Numeracy Literacy for Class V Elementary School Students during the Pandemic - Ujang Efendi; Deviyanti Pangestu; Hasan Hariri; Amalia Berlianti, Rizqi (International Journal of Elementary Education, 2023)
The numeracy literacy of Indonesian students could be higher. Complete learning facilities can support the achievement of student learning outcomes. This study aims to analyze the effect of the learning environment and learning facilities on students' numeracy literacy. This type of research is quantitative with ex-post facto research methods with a survey design. The overall population consists of 24 state primary schools with a total of 523 students. The sampling technique uses cluster sampling. Methods of data collection through questionnaires/questionnaires, questions and document study. The instrument used in this research is a questionnaire. Data analysis in this study uses a simple regression analysis model and multiple regression. The results showed that the learning environment negatively and significantly affected the numeracy literacy of fifth-grade elementary school students. The state of the learning environment around students is quite good, but the response in the form of numeracy literacy learning results is low. Second, the learning environment and facilities influence students' numeracy literacy. Third, the learning environment and facilities negatively and significantly affect numeracy literacy.